Biodegradation of azo dye Orange II using a granular activated carbon (GAC)-biofilm configured biological treatment systems - Ong, Soon-An; Toorisaka, Eiichi; Hirata, Makoto; Hano, Tadashi (Universiti Teknologi Mara (UiTM), 2008)
Organized by Universiti Teknologi Mara (UiTM) Cawangan Pulau Pinang, 8th - 9th December 2006 at UiTM Cawangan Pulau Pinang.